Species Richness and Diversity of Insects in an Argo-ecosystem in Bhabar Region of Uttarakhand - Goswami, Deepika; Rekha; Singh, Vishal (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
The aim of the presented study was to estimate the species richness and diversity of insects were investigated in an agro-ecosystem in Bhabar region of Uttarakhand. In total, 992 individuals were collected representing 7 orders (Lepidoptera, Coleoptera, Hemiptera, Hymenoptera, Orthoptera, Diptera and Odonata), 30 families and 91 species that included herbivores, predators, omnivores and saprophages. The most dominant order was Lepidoptera with a relative abundance of (46.15%) and, the least was Diptera (6.59%). The five most abundant families by numbers of individuals were Pieridae (14.8%), Nymphalidae (13.9%), Lycaenidae (6.1%), Papilionidae (5.9%), and Libellulidae (5.4%). The five most diverse families by species were Nymphalidae (13), Pieridae (9), Lycaenidae (8), Papilionidae (7), and Libellulidae (6). The diversity index showed significant Diversity (Hʹ=1.832), Evenness (E=0.9449) and Margalef species richness (d=2.076) of insect fauna. Diversity indices of insect orders showed that Lepidoptera was the most diverse (Hʹ=1.641), Dipterans had highest Evenness (E=0.9449), and Coleopterans had the maximum species richness as per Margalef’s Index (d=2.056). There were 720 individuals of insect pollinators visitors were observed, which belonged to 62 species in 4 orders (Lepidoptera, Coleoptera, Hymenoptera, and Hemiptera).